Agalliota maculata sp. nov. from Brazil and a key to the species of the genus (Insecta: Hemiptera: Cicadellidae: Agalliinae) - Gonçalves, Ana Clara; Mejdalani, Gabriel; Coelho, Luci B.n. (Zootaxa, 2006)
A new species of the Neotropical genus Agalliota Oman is described and illustrated from southeastern Brazil (Minas Gerais State). Agalliota maculata sp. nov. can be distinguished by its longitudinal pronotal stripes, anal tube processes, and aedeagus shape. With the addition of the new taxon, the number of Agalliota species is increased to eight, seven of them occurring in Brazil. A key to the known species of the genus is provided. Notes on the distinction between Agalliota and Agallia Curtis are given.